Geo-Congress 2022 : Deep Foundations, Earth Retention, and Underground Construction. - Lemnitzer, Anne (American Society of Civil Engineers, 2022)
GSP 332 contains 62 peer-reviewed papers on deep foundations, underground construction, and earth retention presented at Geo-Congress 2022, held in Charlotte, North Carolina, March 20-23, 2022.
Keywords: Geotechnical engineering -- Congresses.; Foundations -- Congresses.; Soil erosion -- Congresses.; Underground construction -- Congresses.; elektronické knihy; electronic books